The Oral Exegesis of Ning Imaz Fatimatuz Zahra (A Study of the Concept of Kafa’ah in Surah An-Nur, Verse 26) - Abdulloh Dardum; Qamaruz Zaman; H. Abdullah (Advances in Humanities and Contemporary Studies, 2025)
The application of the concept of kafa’ah in marriage aims to find equal degrees for each prospective partner in order to achieve sakinah mawaddah warahmah and avoid post-marriage inequality. Ning Imaz Fatimatuz Zahra revealed that kafa’ah serves as a parameter in determining the ideal partner according to personal priorities. Apart from the 4 principles in kafa’ah that have been determined by the scholars, Ning Imaz added two types of considerations that can be used in determining the criteria for the desired prospective partner, namely intellectual and educational scales. This addition was certainly born from her adjustment to the needs of modern society and the journey of her personal experience conveyed in the NU Online channel. This research uses Norman Fairclough’s Critical Discourse Analysis approach with qualitative research methods resulting from the observation of the main source of research in the form of YouTube videos. As a result, it was found that the discourse delivered by Ning Imaz fulfills most of the dimensions of discourse in Norman Fairclough’s level of discourse analysis, namely the textual dimension in the form of several diction in text production. The discourse dimension shows that YouTube is a means of spreading discourse. Finally, the socio-cultural dimension is a factor that influences Ning Imaz’s discourse production related to kafa’ah such as situational, institutional and social levels.